Screening for Squamous Cell Anal Cancer in HIV Positive Patients: A Five-Year Experience. (3rd September 2018) - Santorelli, Chiara; Leo, Cosimo Alex; Hodgkinson, Jonathan D.; Baldelli, Franco; Cantarella, Francesco; Cavazzoni, Emanuel
ABSTRACT: Aim : Potential screening modalities for early diagnosis of squamous cell anal cancer (SCC) in HIV patients include digital anorectal examination (DARE), anal Papanicolaou testing (Pap test), human papilloma virus (HPV) co-testing, and high-resolution anoscopy. The aim of this study was to demonstrate the results of a five-year screening program for SCC in HIV patients. Materials and Methods : We conducted a retrospective study on 204 HIV patients who underwent a screening program for SCC from October 2010 to January 2015. All patients were screened by DARE, anal Pap test, including HPV test and cytology, and high-resolution video-proctoscopy (HR-VPS) with and without acetic acid 3%. Depending on macroscopic appearance and biopsies, patients underwent observation or treatment. Median follow-up was 36 months. Results : Cytologic abnormalities (Cyt+) for high-risk HPV genotypes were recorded in 34% of patients. HR-VPS was positive in 59 patients (29%), of whom 13 patients (22%) were positive for warts; the rest have typical features of anal intraepithelial neoplasia (AIN). Sixteen (8%) patients had AIN (AIN I–III) and underwent wide local excision, ablation, or imiquimod. Absence of progression was recorded. Fourteen patients (7%) had SCC: eight (57%) with no evidence of recurrence, two (14%) had recurrence, and four (29%) died from metastatic disease. Conclusions : Our data demonstrated a successful screening program in preventing SCC in HIV patients. We demonstrate the advantages of progression towards SCC. Moreover, we used a new screening tool, the HR-VPS, a low-cost and manageable instrument to collect patients' long-term data.